2018
DOI: 10.1039/c8nr03137a
|View full text |Cite
|
Sign up to set email alerts
|

Tuning photovoltaic response in Bi2FeCrO6 films by ferroelectric poling

Abstract: Ferroelectric materials are interesting candidates for future photovoltaic applications due to their potential to overcome the fundamental limits of conventional single bandgap semiconductor-based solar cells. Although a more efficient charge separation and above bandgap photovoltages are advantageous in these materials, tailoring their photovoltaic response using ferroelectric functionalities remains puzzling. Here we address this issue by reporting a clear hysteretic character of the photovoltaic effect as a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…Moreover, it is observed that some junctions display nonreversible photoresponse (Supplementary Note 15 and Supplementary Fig. 15), as reported in ferroelectric single crystals and thin films 62,63 , and attributed to charge trapping. It thus follows that, to take full advantage of the photoresponsive ER in FTJs, the ionic transport channel should be mitigated or suppressed.…”
Section: Resultssupporting
confidence: 53%
“…Moreover, it is observed that some junctions display nonreversible photoresponse (Supplementary Note 15 and Supplementary Fig. 15), as reported in ferroelectric single crystals and thin films 62,63 , and attributed to charge trapping. It thus follows that, to take full advantage of the photoresponsive ER in FTJs, the ionic transport channel should be mitigated or suppressed.…”
Section: Resultssupporting
confidence: 53%
“…2). The c out of plane lattice parameters calculated from the two maps are of 0.3962(4) and 0.3963(4) nm while the in plane parameters are 0.3898(3) and 0.3906(2) nm. This result clearly show that the film is fully strained on the STO substrate (0.3906 nm).…”
mentioning
confidence: 94%
“…13 Note also that the gap can be modulated to some extent by controlling the Fe-Cr order, 14 resulting in a conversion efficiency that is dependent on the poling history. 2 In this context, the study of the polarization reversal in BFCO and the resulting electron conduction is essential to understand the mechanisms governing the energy conversion in solar cells or other ferroelectric applications.…”
Section: Introductionmentioning
confidence: 99%
“…This proves that research on novel materials for solar cells can be quite successful and should be maintained. Standard solar cells are based on a pn-junction, however ferroelectric solar cells have emerged with a record conversion efficiency in Bi 2 FeCrO 6 of 8.1% (1,2,3).…”
Section: Introductionmentioning
confidence: 99%